High-thermal-conductivity organic silicon two-component pouring sealant and preparation method thereof

By using the combination of double-modified sheet α-alumina and spherical aluminum trioxide as thermal filler in silicone thermal potting glue, the problem of insufficient filler addition is solved, and the problem of insufficient thermal conductivity and excessive hardness is increased, achieving both high thermal conductivity and good mechanical properties.

CN119859505APending Publication Date: 2025-04-22SUZHOU HEBANG NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510166396.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing silicone thermal potting glue is insufficient when the filler is added, and the hardness increases and the mechanical properties decrease when the filler is added too much, making it difficult to meet the needs of high thermal conductivity.

Method used

The combination of bimodified sheet-shaped α-alumina and spherical alumina is used as the modified thermal conductivity filler. By modifying tannin acid and coupling agent, the compatibility and bonding strength of the filler are improved, and the construction ability of the thermal conductivity path is enhanced.

Benefits of technology

While reducing the amount of filler addition, the thermal conductivity of thermally conductive silicone is significantly improved, while maintaining good mechanical properties and low hardness, with price advantages and low operating costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005272584050000121
    Figure BDA0005272584050000121
Patent Text Reader

Abstract

The invention relates to a high-thermal-conductivity organosilicon bi-component pouring sealant and a preparation method thereof, and belongs to the technical field of thermal-conductive pouring sealants. The high-thermal-conductivity organosilicone two-component pouring sealant provided by the invention comprises a component A and a component B. The component A comprises the following components in parts by weight: 50 parts of vinyl silicone oil, 60-90 parts of a modified thermal conductive filler and 0.01-0.05 part of a catalyst; the component B comprises 1-4 parts of hydrogen-containing silicone oil, 50 parts of vinyl silicone oil and 60-90 parts of modified heat-conducting filler; the modified heat-conducting filler comprises a combination of dual-modified flaky alpha-aluminum oxide and spherical aluminum oxide; the dual-modified flaky alpha-aluminum oxide is obtained by modifying flaky alpha-aluminum oxide with tannic acid and a coupling agent. The organic silicon pouring sealant provided by the invention has the advantages of high thermal conductivity, excellent mechanical property, low hardness and wide market application prospect, and a feasible scheme is provided for improving the thermal conductivity of organic silica gel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal conductive potting adhesives, and in particular to a high thermal conductive organic silicon two-component potting adhesive and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of electronic technology, electronic equipment is developing rapidly towards high performance, high integration, light weight, miniaturization and diversified functions. This trend has been widely used and promoted in various fields. As the power of electronic equipment continues to increase, the heat generated by various components during operation also increases sharply. The heat dissipation performance of materials is crucial to the stable operation and service life of components. During the use of electronic equipment, components will inevitably generate a lot of heat. If this heat cannot be conducted in time and quickly and efficiently diffused, the life of the device will be shortened or even the function will fail.

[0003] Thermal interface material is a material that fills the interface between electronic devices (such as chips) and solid interfaces such as heat sinks, and is widely used in the field of electronic packaging. Addition-type thermal conductive silicone is a flexible material composed of organic silicone and thermal conductive fillers. In addition to the excellent high and low temperature resistance, weather resistance, electrical insulation, moisture resistance and corrosion resistance of general addition-type silicone rubber, its softness also gives the material a low elastic modulus and low internal stress. However, the intrinsic thermal conductivity of polymers is low (about 0.1-0.4W·m -1 K -1 ), the simplest way to make silicone thermally conductive is to add thermally conductive fillers. Currently, the commonly used addition-type thermally conductive silicone on the market can meet the conventional requirements of thermal conductivity (>1.5W·m -1 K -1 ), but the demand for higher thermal conductivity still faces some challenges. Aluminum oxide has become the most commonly used thermal conductive filler due to its price advantage. However, most of the aluminum oxide fillers on the market are spherical. Although spherical fillers are easier to mix evenly with resins and achieve good dispersion effects, their spherical structure has certain limitations on the construction of thermal conductive paths, and the addition of too much thermal conductive filler will affect the hardness of the silicone material itself.

[0004] Compared with spherical fillers, flake thermal conductive fillers are relatively easier to construct thermal conductive paths, so they can have stronger thermal conductivity. However, due to the dispersion problem, it is difficult to increase the amount of flake thermal conductive fillers added, and the thermal conductivity of the resulting product is also relatively limited, which limits the application of flake aluminum oxide in the field of high thermal conductivity.

[0005] Therefore, how to improve the dispersibility of flaky thermal conductive fillers in thermal conductive silicone rubber so as to meet the high thermal conductivity requirements of silicone thermal conductive potting adhesive while reducing the amount of filler added, while maintaining the low hardness of the silicone rubber itself, is still an urgent problem to be solved. Summary of the invention

[0006] In view of the problems that the thermal conductivity of the existing silicone thermal conductive potting glue is insufficient when too little filler is added, and the hardness increases and the mechanical properties decrease when too much filler is added, the present application provides a high thermal conductive silicone two-component potting glue and a preparation method thereof.

[0007] On the one hand, the present application provides a high thermal conductivity two-component silicone potting adhesive, including component A and component B, which are calculated by weight.

[0008] The component A comprises 50 parts of vinyl silicone oil, 60-90 parts of modified thermal conductive filler, and 0.01-0.05 parts of catalyst;

[0009] The B component includes 1 to 4 parts of hydrogenated silicone oil, 50 parts of vinyl silicone oil, and 60 to 90 parts of modified thermal conductive filler;

[0010] The modified thermal conductive filler comprises a combination of double-modified flake α-aluminum oxide and spherical aluminum oxide;

[0011] The double-modified flaky α-aluminum oxide is obtained by modifying flaky α-aluminum oxide with tannic acid and a coupling agent.

[0012] Furthermore, the preparation steps of the double-modified flaky α-alumina are:

[0013] Step 1: dissolve tannic acid in water, add inorganic base to prepare sodium salt / potassium salt of tannic acid, then add flaky α-alumina, disperse by ultrasonic, stir at room temperature for 24-48 hours, filter, wash three times with deionized water, and dry to obtain single-modified flaky α-alumina;

[0014] Step 2: Ultrasonic dispersion of the singly modified flaky α-alumina and the silane coupling agent in an alcohol solvent, stirring at room temperature for 6 to 48 hours, filtering, washing three times with an alcohol solvent, and drying to obtain the doubly modified flaky α-alumina.

[0015] Further, the silane coupling agent includes one or more of 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, hexamethyldisilazane, polymethyltriethoxysilane, and vinyltri-tert-butylperoxide silane;

[0016] Furthermore, the molar ratio of the tannic acid to the inorganic base compound is 1:(26-29);

[0017] The mass ratio of the flaky α-aluminum oxide to tannic acid is 1:(5-7);

[0018] The mass ratio of the single modified flaky α-aluminum oxide to the silane coupling agent is 1:(0.7-0.9).

[0019] Further, the inorganic base includes sodium carbonate, potassium carbonate, sodium bicarbonate or potassium bicarbonate;

[0020] The alcohol solvent includes methanol, ethanol and isopropanol;

[0021] The flaky α-aluminum oxide has a micro-flake size of 1 to 5 μm and a thickness of 0.8 to 1.2 nm.

[0022] Furthermore, the molar ratio of hydrogen in the hydrogen-containing silicone oil to vinyl in the vinyl silicone oil is between 1:(1.1-1.6);

[0023] The vinyl silicone oil contains 0.4-0.6% vinyl by mass and has a viscosity of 200-600cps;

[0024] The hydrogen-containing silicone oil includes side hydrogen-containing silicone oil; the hydrogen content of the side hydrogen-containing silicone oil is 0.01-1.55%, and the viscosity is 100-500cps.

[0025] Furthermore, the component A and the component B also include 20 to 30 parts of double-modified flaky α-alumina and 40 to 60 parts of spherical alumina.

[0026] Furthermore, the added mass ratio of the double-modified flaky α-alumina to the spherical alumina is (0.3-0.7):1, preferably (0.4-0.6):1.

[0027] Furthermore, the catalyst includes a platinum catalyst.

[0028] The second aspect of the present invention provides a method for preparing the high thermal conductivity organic silicone two-component potting adhesive according to the first aspect, characterized in that it comprises the following steps:

[0029] The vinyl silicone oil, the modified thermal conductive filler and the catalyst are uniformly mixed and vacuum degassed to obtain component A;

[0030] The hydrogen-containing silicone oil, vinyl silicone oil and modified thermal conductive filler are mixed evenly, and the component B is obtained after vacuum degassing;

[0031] The component A and the component B are packaged and sealed in double barrels or double tubes in a mass ratio of 1:1 to obtain the high thermal conductive organic silicone two-component potting adhesive.

[0032] Beneficial effects of the present invention:

[0033] The high thermal conductivity organic silicon two-component potting glue provided by the present application realizes the increase of the amount of thermal conductive filler added in the organic silicon system by modifying the thermal conductive filler; by adding a combination of double-modified flake α-aluminum trioxide and spherical aluminum trioxide, and then utilizing the characteristic that the flake filler is easier to overlap the thermal conductive path, the thermal conductivity of the thermal conductive silicone is greatly improved at the same addition amount, while maintaining good mechanical properties and low hardness. In addition, the solution has significant price advantages and low operating costs, showing excellent market application prospects.

[0034] In the modification of the thermal conductive filler in this application, tannic acid is modified to produce a strong π-π bond between α-aluminum oxide and tannic acid, thereby introducing a large number of hydroxyl groups on the surface of the thermal conductive filler. The bonding strength of a large number of hydroxyl groups to the matrix will also be improved, so that the thermal conductive silicone rubber finally prepared has a stronger bonding strength than when no thermal conductive filler is added; the increase in the hydroxyl content also increases the amount of coupling agent added, and the addition of the coupling agent makes the thermal conductive filler and the silicone matrix more compatible. The modification of the flaky α-aluminum oxide effectively reduces the thermal interface thermal resistance of the system and increases the compatibility, providing a feasible implementation plan for improving the high thermal performance of thermal conductive silicone rubber. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0036] The present application provides a high thermal conductivity organic silicon two-component potting adhesive, comprising component A and component B, wherein the component A comprises 50 parts of vinyl silicone oil, 60 to 90 parts of modified thermal conductive filler, such as 60, 65, 70, 75, 80, 85, 90 parts by weight or any value therebetween, and 0.01 to 0.05 parts of catalyst, such as 0.01, 0.02, 0.03, 0.04, 0.05 parts by weight or any value therebetween.

[0037] The B component includes 1 to 4 parts of hydrogen-containing silicone oil, such as 1, 1.5, 2, 2.5, 3, 3.5, 4 parts by weight or any value therebetween; 50 parts of vinyl silicone oil; 60 to 90 parts of modified thermal conductive filler, such as 60, 65, 70, 75, 80, 85, 90 parts by weight or any value therebetween;

[0038] The modified thermal conductive filler comprises a combination of double-modified flake α-aluminum oxide and spherical aluminum oxide;

[0039] The double-modified flaky α-aluminum oxide is obtained by modifying flaky α-aluminum oxide with tannic acid and a coupling agent.

[0040] In this embodiment, thermal conductivity of the polymer is achieved by adding thermally conductive fillers. The combination of spherical alumina and modified α-alumina can form a good thermal conductivity path in the polymer, so that the cured polymer has excellent thermal conductivity. At the same time, the mechanical properties are also improved due to the synergistic effect of the combination of various components. Due to the price advantage of raw material costs, a feasible thermal conductive silicone solution is provided for practical applications.

[0041] In some embodiments of the present invention, the preparation steps of the double-modified flaky α-alumina are:

[0042] Step 1: dissolve tannic acid in water, add inorganic base to prepare sodium salt / potassium salt of tannic acid, then add flaky α-alumina, disperse by ultrasonic, stir at room temperature for 24-48 hours, filter, wash three times with deionized water, and dry to obtain single-modified flaky α-alumina;

[0043] Step 2: Ultrasonic dispersion of the singly modified flaky α-alumina and the silane coupling agent in an alcohol solvent, stirring at room temperature for 6 to 48 hours, filtering, washing three times with an alcohol solvent, and drying to obtain the doubly modified flaky α-alumina.

[0044] In this embodiment, in the modification of the thermal conductive filler, tannic acid is modified to produce a strong π-π bond with α-aluminum oxide and tannic acid, thereby introducing a large number of hydroxyl groups on the surface of the thermal conductive filler. The bonding strength of a large number of hydroxyl groups to the matrix is ​​also improved, so that the thermal conductive silicone rubber finally prepared has a stronger bonding strength than that without thermal conductive filler; the increase in hydroxyl content also increases the amount of coupling agent added, and the addition of coupling agent makes the thermal conductive filler and the silicone matrix more compatible. The modification of the flaky α-aluminum oxide effectively reduces the thermal interface thermal resistance of the system and increases the compatibility, providing a feasible implementation plan for improving the high thermal performance of thermal conductive silicone rubber.

[0045] In some embodiments of the present invention, the silane coupling agent includes one or more of 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, hexamethyldisilazane, polymethyltriethoxysilane, and vinyltri-tert-butylperoxide silane;

[0046] In a preferred embodiment, the silane coupling agent is polymethyltriethoxysilane.

[0047] In some embodiments of the present invention, the molar ratio of the tannic acid to the inorganic base compound is 1:(26-29), such as 1:26, 1:27, 1:28, 1:29 or any value therebetween;

[0048] In a preferred embodiment, the molar ratio of the tannic acid to the inorganic base compound is 1:27.

[0049] In some embodiments of the present invention, the mass ratio of the flaky α-aluminum oxide to tannic acid is 1:(5-7), such as 1:5, 1:5.5, 1:6, 1:6.5, 1:7 or any value therebetween;

[0050] In a preferred embodiment, the mass ratio of the flaky α-aluminum oxide to tannic acid is 1:5.

[0051] In some embodiments of the present invention, the mass ratio of the single-modified flaky α-aluminum oxide and the silane coupling agent is 1:(0.7-0.9), such as 1:0.7, 1:0.75, 1:0.8, 1:0.85, 1:0.9 or any value therebetween;

[0052] In a preferred embodiment, the mass ratio of the single-modified flaky α-aluminum oxide to the silane coupling agent is 1:0.8.

[0053] In some embodiments of the present invention, the inorganic base includes sodium carbonate, potassium carbonate, sodium bicarbonate or potassium bicarbonate;

[0054] In a preferred embodiment, the inorganic base is sodium bicarbonate.

[0055] The alcohol solvent includes methanol, ethanol and isopropanol;

[0056] In a preferred embodiment, the alcohol solvent is methanol.

[0057] The flaky α-aluminum oxide has a micro-flake size of 1 to 5 μm and a thickness of 0.8 to 1.2 nm.

[0058] In some embodiments of the present invention, the molar ratio of hydrogen in the hydrogen-containing silicone oil to vinyl in the vinyl silicone oil is between 1:(1.1-1.6), such as 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, :1.6 or any value therebetween;

[0059] The vinyl silicone oil contains 0.4-0.6% vinyl by mass and has a viscosity of 200-600cps;

[0060] The hydrogen-containing silicone oil includes side hydrogen-containing silicone oil; the hydrogen content of the side hydrogen-containing silicone oil is 0.01-1.55%, and the viscosity is 100-500cps.

[0061] In some embodiments of the present invention, the A component and the B component also include 20 to 30 parts of double-modified flaky α-alumina, such as 20, 22, 23, 25, 27, 30 parts by weight or any value therebetween; and 40 to 60 parts of spherical oxide, such as 40, 42, 46, 48, 50, 52, 54, 56, 58, 60 parts by weight or any value therebetween;.

[0062] In some embodiments of the present invention, the added mass ratio of the double-modified flaky α-alumina to the spherical alumina is (0.3-0.7):1, such as 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1 or any value therebetween, preferably (0.4-0.6):1.

[0063] In this embodiment, when the amount of double-modified flaky α-alumina added is too much, it will exceed the compatibility with the base glue, causing the agglomeration and sedimentation of the thermal conductive filler, which has a negative impact on both the thermal conductivity and mechanical properties. In this application, the amount and proportion of the thermal conductive filler were further explored, and it was found that the comprehensive performance was optimal when the mass ratio of flaky α-alumina to spherical alumina was 0.5:1.

[0064] In some embodiments of the present invention, the catalyst comprises a platinum catalyst.

[0065] In a preferred embodiment, the catalyst is a divinyltetramethyldisiloxane platinum complex.

[0066] The present invention also provides a method for preparing a high thermal conductive organic silicon two-component potting adhesive, which is characterized by comprising the following steps:

[0067] The vinyl silicone oil, the modified thermal conductive filler and the catalyst are uniformly mixed and vacuum degassed to obtain component A;

[0068] The hydrogen-containing silicone oil, vinyl silicone oil and modified thermal conductive filler are mixed evenly, and the component B is obtained after vacuum degassing;

[0069] The component A and the component B are packaged and sealed in double barrels or double tubes in a mass ratio of 1:1 to obtain the high thermal conductive organic silicone two-component potting adhesive.

[0070] The raw materials and sources used in the following examples and comparative examples are as follows:

[0071] Tannic acid, brand name Adamas, comes from Titan; Aluminum oxide: flaky α-aluminum oxide, brand name DCA-01W, comes from Dongguan Dongchao New Materials Technology Co., Ltd.; Polymethyltriethoxysilane, brand name CG-1204, comes from Jiangxi Chenguang New Materials Co., Ltd.; Hydrogenated silicone oil, comes from Dongguan Dongsheng Synthetic Materials Co., Ltd.; Platinum catalyst, divinyltetramethyldisiloxane platinum complex, comes from Dongguan Dongsheng Synthetic Materials Co., Ltd.

[0072] Preparation Example 1

[0073] Step 1: Take 500g of tannic acid and dissolve it in 1000mL of water. After stirring evenly, add 670g of sodium bicarbonate in batches to prepare tannic acid sodium salt; then add 100g of flaky α-alumina into the system, ultrasonically disperse it, and stir it at room temperature for 24h; filter it, wash it three times with deionized water, and then dry it at 50°C for 24h to obtain the single-modified flaky α-alumina.

[0074] Step 2: Weigh 500 g of modified aluminum oxide A and 400 g of polymethyltriethoxysilane, ultrasonically disperse them in 1000 mL of methanol, stir at room temperature for 12 h, filter, wash three times with methanol, and then dry at 50° C. for 24 h to obtain double-modified flaky α-alumina.

[0075] Example 1

[0076] 50 parts of vinyl silicone oil, 25 parts of double-modified flaky α-aluminum oxide, 50 parts of spherical aluminum oxide, and 0.2 parts of a catalyst are mixed evenly, and vacuum degassing is performed to obtain component A;

[0077] 2.6 parts of hydrogen silicone oil, 50 parts of vinyl silicone oil, 25 parts of double-modified flaky α-aluminum trioxide, and 50 parts of spherical aluminum trioxide are vacuum degassed to obtain component B;

[0078] The component A and the component B are packaged and sealed in double barrels or double tubes in a mass ratio of 1:1 to obtain a high thermal conductive two-component silicone potting adhesive.

[0079] Example 2

[0080] Most of the steps of this embodiment are the same as those of embodiment 1, except that 1.6 parts of hydrogenated silicone oil are added to component B.

[0081] Example 3

[0082] Most of the steps of this embodiment are the same as those of embodiment 1, except that 2.2 parts of hydrogenated silicone oil are added to component B.

[0083] Example 4

[0084] Most of the steps of this embodiment are the same as those of embodiment 1, except that 3.0 parts of hydrogen-containing silicone oil are added to component B.

[0085] Example 5

[0086] Most of the steps of this embodiment are the same as those of Embodiment 1, except that: 20 parts of double-modified flaky α-alumina and 40 parts of spherical alumina are added to component A; 20 parts of double-modified flaky α-alumina and 40 parts of spherical alumina are added to component B.

[0087] Example 6

[0088] Most of the steps of this embodiment are the same as those of Embodiment 1, except that: 23 parts of double-modified flaky α-alumina and 45 parts of spherical alumina are added to component A; 23 parts of double-modified flaky α-alumina and 45 parts of spherical alumina are added to component B.

[0089] Example 7

[0090] Most of the steps of this embodiment are the same as those of Embodiment 1, except that: 27 parts of double-modified flaky α-alumina and 55 parts of spherical alumina are added to component A; 27 parts of double-modified flaky α-alumina and 55 parts of spherical alumina are added to component B.

[0091] Example 8

[0092] Most of the steps of this embodiment are the same as those of Embodiment 1, except that: 30 parts of double-modified flaky α-alumina and 60 parts of spherical alumina are added to component A; 30 parts of double-modified flaky α-alumina and 60 parts of spherical alumina are added to component B.

[0093] Example 9

[0094] Most of the steps of this embodiment are the same as those of Embodiment 1, except that: 15 parts of double-modified flaky α-alumina and 30 parts of spherical alumina are added to component A; 15 parts of double-modified flaky α-alumina and 30 parts of spherical alumina are added to component B.

[0095] Example 10

[0096] Most of the steps of this embodiment are the same as those of Embodiment 1, except that: 33 parts of double-modified flaky α-alumina and 65 parts of spherical alumina are added to component A; 33 parts of double-modified flaky α-alumina and 65 parts of spherical alumina are added to component B.

[0097] Embodiment 11

[0098] Most of the steps of this embodiment are the same as those of embodiment 1, except that 30 parts of double-modified flaky α-alumina are added to component A; and 30 parts of double-modified flaky α-alumina are added to component B.

[0099] Example 12

[0100] Most of the steps of this embodiment are the same as those of embodiment 1, except that 20 parts of double-modified flaky α-alumina are added to component A; and 20 parts of double-modified flaky α-alumina are added to component B.

[0101] Embodiment 13

[0102] Most of the steps of this embodiment are the same as those of embodiment 1, except that 35 parts of double-modified flaky α-alumina are added to component A; and 35 parts of double-modified flaky α-alumina are added to component B.

[0103] Embodiment 14

[0104] Most of the steps of this embodiment are the same as those of embodiment 1, except that 15 parts of double-modified flaky α-alumina are added to component A; and 15 parts of double-modified flaky α-alumina are added to component B.

[0105] Comparative Example 1

[0106] 50 parts of vinyl silicone oil, 50 parts of spherical aluminum oxide, 25 parts of biflaky α-aluminum oxide and 0.2 parts of a catalyst are mixed evenly, and vacuum degassing is performed to obtain component A;

[0107] 2.6 parts of hydrogen silicone oil, 50 parts of vinyl silicone oil, 50 parts of spherical aluminum oxide, and 25 parts of flaky α-aluminum oxide are vacuum degassed to obtain component B;

[0108] The component A and the component B are packaged and sealed in double barrels or double tubes in a mass ratio of 1:1 to obtain a two-component silicone potting adhesive.

[0109] Comparative Example 2

[0110] 50 parts of vinyl silicone oil, 50 parts of spherical aluminum oxide, 25 parts of double-mono-modified flake α-aluminum oxide, and 0.2 parts of a catalyst were mixed evenly, and vacuum degassing was performed to obtain component A;

[0111] 2.6 parts of hydrogen silicone oil, 50 parts of vinyl silicone oil, 50 parts of spherical aluminum oxide, and 25 parts of single-modified flaky α-aluminum oxide are vacuum degassed to obtain component B;

[0112] The component A and the component B are packaged and sealed in double barrels or double tubes in a mass ratio of 1:1 to obtain a two-component silicone potting adhesive.

[0113] Comparative Example 3

[0114] 50 parts of vinyl silicone oil, 75 parts of spherical aluminum oxide and 0.2 parts of a catalyst were mixed evenly, and component A was obtained after vacuum degassing;

[0115] 2.6 parts of hydrogen silicone oil, 50 parts of vinyl silicone oil and 75 parts of spherical aluminum oxide are vacuum degassed to obtain component B;

[0116] The component A and the component B are packaged and sealed in double barrels or double tubes in a mass ratio of 1:1 to obtain a two-component silicone potting adhesive.

[0117] Comparative Example 4

[0118] 50 parts of vinyl silicone oil and 0.2 parts of catalyst were mixed evenly, and component A was obtained after vacuum degassing;

[0119] 2.6 parts of hydrogen silicone oil and 50 parts of vinyl silicone oil were vacuum degassed to obtain component B;

[0120] The component A and the component B are packaged and sealed in double barrels or double tubes in a mass ratio of 1:1 to obtain a two-component silicone potting adhesive.

[0121] Performance Testing

[0122] The high thermal conductivity organic silicon two-component potting adhesives prepared in the above-mentioned embodiments and comparative examples were subjected to the following performance tests.

[0123] Curing conditions: Mix component A and component B in a mass ratio of 1:1, then pour the mixed glue into the mold and cure at 80℃ for 3h to obtain the test sample.

[0124] 1. Hardness: The sample was measured according to GB / T 531.1-2008 standard. The sample size was 25.0 mm × 25.0 mm and the thickness was 6.0 mm.

[0125] 2. Tensile shear strength: According to GB / T 7124-2008 standard, the samples were tested using a universal electronic tensile testing machine. The size of the aluminum sheet substrate is 100mm×25.0mm×2mm, and the size of the adhesive surface is 12.5mm×25.5mm.

[0126] 3. Viscosity (40℃)

[0127] Test preparation: Mix component A and component B in a mass ratio of 1:1, and then pour the mixed liquid into a constant temperature test cup.

[0128] Test steps: During the test, the temperature must be kept constant at 40°C and a digital viscometer is used for testing. The process is based on standard GB / T 2794-2013.

[0129] 4. Thermal conductivity

[0130] Sample requirements: diameter 30mm, thickness ≤5mm, and smooth surface. Coat a layer of thermal conductive silicone grease on the surface of the prepared sample, then put it into the equipment to start testing. The test process is carried out according to the standard ASTM D5470. The equipment used for the test is Xiangtan Instrument DRL-V thermal conductivity tester, with a cold pole temperature of 30℃, a hot pole temperature of 70℃, and a test pressure of 200N.

[0131] The test results are shown in Table 1.

[0132] Table 1 Performance test results of examples and comparative examples

[0133]

[0134]

[0135] Combined with the data analysis in Table 1, it can be seen from Comparative Example 4 that the silicone system does not have thermal conductivity without adding thermal conductive fillers. Comparing Example 1 and Comparative Example 1, it can be seen that when the same number of flaky α-alumina is added, since the thermal conductive filler added in Comparative Example 1 does not modify the flaky α-alumina, the viscosity of the silicone two-component potting glue will become very large, reaching 5300cps, and the thermal conductivity coefficient is only 1.2W / m·k. The hardness after curing is 90A, and the hardness becomes larger, which is no longer suitable for potting. Comparison of Example 1, Comparative Example 1 and Comparative Example 2 shows that although the thermal conductivity is improved by adding a single modified flaky α-alumina, the compatibility with the substrate is still poor, and the viscosity is relatively large, resulting in a high hardness after the final curing, which affects the mechanical properties and limits the degree of improvement in tensile shear strength.

[0136] It can be seen from Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 that when only spherical alumina is added, the thermal conductivity can only reach 1 W / m·k, indicating that when only spherical alumina is added, although the mechanical properties and hardness of the substrate are not greatly affected, the improvement of thermal conductivity is limited, so it is difficult to achieve a higher thermal conductivity when the spherical thermal conductive filler builds a thermal conductive path.

[0137] By comparing Examples 1-4, it can be seen that when the silicon-hydrogen ratio is changed, that is, when the amount of hydrogen-containing silicone oil added is different, when the molar ratio of hydrogen in the hydrogen-containing silicone oil to vinyl in the vinyl silicone oil is 1:1.4 in Example 1, the comprehensive performance is optimal. When too much or too little hydrogen-containing silicone oil is added, it will affect the mechanical properties due to the influence on the crosslinking density during the curing of the thermal conductive silicone.

[0138] By comparing Example 1 and Examples 5-14, it can be seen that the ratio and content of the added double-modified flaky α-alumina and spherical alumina are crucial to the performance. The performance is optimal when the mass ratio of the added double-modified flaky α-alumina and spherical alumina is 0.5:1. When the added double-modified flaky α-alumina is reduced, the heat conduction path cannot be well overlapped, resulting in a decrease in thermal conductivity; when the added double-modified flaky α-alumina increases, the compatibility with the matrix is ​​reduced, resulting in reduced mechanical properties and lower thermal conductivity.

[0139] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, it should be understood by those skilled in the art that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention.

Claims

1. A high thermal conductivity silicone two-component potting compound, characterized in that: Including component A and component B, in parts by weight, The component A comprises 50 parts of vinyl silicone oil, 60-90 parts of modified thermal conductive filler, and 0.01-0.05 parts of catalyst; The B component includes 1 to 4 parts of hydrogenated silicone oil, 50 parts of vinyl silicone oil, and 60 to 90 parts of modified thermal conductive filler; The modified thermal conductive filler comprises a combination of double-modified flake α-aluminum oxide and spherical aluminum oxide; The double-modified flaky α-aluminum oxide is obtained by modifying flaky α-aluminum oxide with tannic acid and a coupling agent.

2. The high thermal conductivity organic silicon two-component potting adhesive according to claim 1, characterized in that: The preparation steps of the double-modified flaky α-alumina are as follows: Step 1: dissolve tannic acid in water, add inorganic base to prepare sodium salt / potassium salt of tannic acid, then add flaky α-alumina, disperse by ultrasonic, stir at room temperature for 24-48 hours, filter, wash three times with deionized water, and dry to obtain single-modified flaky α-alumina; Step 2: Ultrasonic dispersion of the singly modified flaky α-alumina and the silane coupling agent in an alcohol solvent, stirring at room temperature for 6 to 48 hours, filtering, washing three times with an alcohol solvent, and drying to obtain the doubly modified flaky α-alumina.

3. The high thermal conductivity organic silicon two-component potting adhesive according to claim 2, characterized in that: The silane coupling agent includes one or more of 3-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-thiolpropyltriethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, hexamethyldisilazane, polymethyltriethoxysilane, and vinyltri-tert-butylperoxide silane.

4. The high thermal conductivity organic silicon two-component potting adhesive according to claim 2, characterized in that: The molar ratio of the tannic acid to the inorganic base compound is 1:(26-29); The mass ratio of the flaky α-aluminum oxide to tannic acid is 1:(5-7); The mass ratio of the single modified flaky α-aluminum oxide to the silane coupling agent is 1:(0.7-0.9).

5. The high thermal conductivity organic silicon two-component potting adhesive according to claim 2, characterized in that: The inorganic base includes sodium carbonate, potassium carbonate, sodium bicarbonate or potassium bicarbonate; The alcohol solvent includes methanol, ethanol and isopropanol; The flaky α-aluminum oxide has a micro-flake size of 1 to 5 μm and a thickness of 0.8 to 1.2 nm.

6. The high thermal conductivity organic silicon two-component potting adhesive according to claim 1, characterized in that: The molar ratio of hydrogen in the hydrogen-containing silicone oil to vinyl in the vinyl silicone oil is between 1:(1.1-1.6); The vinyl silicone oil contains 0.4-0.6% vinyl by mass and has a viscosity of 200-600 cps; The hydrogen-containing silicone oil includes side hydrogen-containing silicone oil; the hydrogen content of the side hydrogen-containing silicone oil is 0.01-1.55%, and the viscosity is 100-500cps.

7. The high thermal conductivity organic silicon two-component potting adhesive according to claim 1, characterized in that: The A component and the B component also include 20 to 30 parts of double-modified flaky α-alumina and 40 to 60 parts of spherical alumina.

8. The high thermal conductivity organic silicon two-component potting adhesive according to claim 1, characterized in that The added mass ratio of the double-modified flaky α-alumina to the spherical alumina is (0.3-0.7):

1.

9. The high thermal conductivity organic silicon two-component potting adhesive according to claim 1, characterized in that: The catalyst includes a platinum catalyst.

10. A method for preparing the high thermal conductivity organic silicon two-component potting adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: The vinyl silicone oil, the modified thermal conductive filler and the catalyst are uniformly mixed and vacuum degassed to obtain component A; The hydrogen-containing silicone oil, vinyl silicone oil and modified thermal conductive filler are mixed evenly, and the component B is obtained after vacuum degassing; The component A and the component B are packaged and sealed in double barrels or double tubes in a mass ratio of 1:1 to obtain the high thermal conductive organic silicone two-component potting adhesive.